The Effect of Spatial Ability on the Mastery of Mathematical Concepts for Class VIII MTs Nahdlatul Mujahidin NW Jempong - Dedi Sopyan; M. Gunawan Supiarmo (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2022)
Spatial ability includes students' skills to understand in depth the relationship between objects and space, so that it can help improve students' understanding of concepts. Spatial ability is a type of skill that requires high-level thinking processes in imagining geometrical architecture through a strong imagination. These skills can make it easier for students to master mathematical concepts in order to solve problems correctly. This study aims to determine the effect of mathematical spatial ability on students' conceptual mastery. This study uses a quantitative approach with a type of expost facto research. The instrument used consisted of a test of spatial ability in the form of multiple choice with a total of 20 items, while to determine the mastery of students' concepts, a description test of 5 items was used. This research was conducted at MTs Nahdlatul Mujahidin NW Jempong with a population of class VIII and a sample of 25 students from class VIII A and class VIII B. tcount = 0.90, consequently tcount is greater than ttable, then Ha is accepted. Based on the determination test, it is known that the value of R2 = 0.81. This means that spatial ability can affect students' mastery of concepts by 81%, while 19% is influenced by other factors not examined. The regression equation is Y = 37.88 + 0.63X which indicates that there is a positive effect.